Relation of neuropathology with cognitive decline among older persons without dementia - Boyle, Patricia; Yu, Lei; Wilson, Robert; Schneider, Julie; Bennett, David A. (Frontiers in Aging Neuroscience, 2013)
Objective: Although it is now widely accepted that dementia has a long preclinical phase during which neuropathology accumulates and cognition declines, little is known about the relation of neuropathology with the longitudinal rate of change in cognition among older persons without dementia. We quantified the burden of the neuropathologies of the three most common causes of dementia (i.e., Alzheimer’s disease (AD), cerebrovascular disease (CVD), and Lewy body disease (LBD)) and examined their relation with cognitive decline in a large cohort of persons without dementia proximate to death. Methods: 467 deceased participants without dementia from two longitudinal clinical-pathologic studies, Rush Memory and Aging Project and Religious Orders Study, completed a mean of 7 annual evaluations including 17 cognitive tests. Neuropathologic examinations provided quantitative measures of AD (i.e., amyloid load, tangle density), CVD (i.e., macroscopic infarcts, microinfarcts), and neocortical Lewy bodies. Random coefficient models were used to examine the relation of the neuropathologies with rates of global cognitive decline as well as decline in 4 specific cognitive systems. Results: At autopsy, 82% of persons without dementia had amyloid, 100% had tangles, 29% had macroscopic infarcts, 25% had microinfarcts, and 6% had neocortical Lewy bodies. Global cognition declined a mean of 0.034 unit per year (SE=0.003, p<0.001). In separate analyses, amyloid, tangles (p-values<0.001) and neocortical Lewy bodies (p=0.015) were associated with an increased rate of global cognitive decline; macroscopic infarcts and microinfarcts were not. Further, when analyzed simultaneously, amyloid, tangles, and neocortical Lewy bodies remained associated with global cognitive decline (p- values<0.024). Finally, measures of AD were associated with decline in 3 of 4 systems, including episodic memory (i.e., tangles), semantic memory (i.e., amyloid and tangles), and working memory (i.e., amy